ANALISIS DAMPAK PENGGUNAAN RUANG TERHADAP RISIKO PERUBAHAN IKLIM: STUDI KASUS PROVINSI LAMPUNG - Najmulmunir, Nandang (Magister Ilmu Pemerintahan, Program Pascasarjana Universitas Islam, 2011)
The global climate change was the main global environmental problem. It was influenced by increasing the green house gas. The CO2 gas is of this one. The global climate change is accumulated factor from regional level to local level changes. The main factor is land use and cover change. These changes correlated by decreasing the capacity of the nature in the sink of CO2 gas and the increasing the emitting of the CO2 to the atmosphere. The agriculture practices in the regional development economic always do high risk of environmental problems.